DESENTRALISASI DAN DEMOKRASI - Mudiyati Rahmatunnisa (Governance, 2011)
Decentralization and democracy are complex concepts. Contemporary discourse shows that both concepts have the potential of symbiotic relationship. However, theoretical and empirical discourse shows that the claim is not without opposition. This paper discusses the two concepts, the potential for symbiotic relationships between them, as well as criticism that appear on the relationship between the two concepts from various experts.